2020
DOI: 10.1155/2020/5410263
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance between Histidine-Rich Protein 2 (HRP-2), a Rapid Malaria Diagnostic Test and Microscopic-Based Staining Techniques for Diagnosis of Malaria

Abstract: Malaria presents a diagnostic challenge in most tropical countries such as Rwanda. Microscopy remains the gold standard for diagnosing malaria, but it is labor intensive and depends upon the skill of the examiner. Malaria rapid diagnostic tests (RDTs) have been developed as an easy, convenient alternative to microscopy. is cross-sectional study was conducted at Rukara Health Center which is located in Eastern Province, Kayonza district, Rwanda. One hundred and fifty suspected cases of malaria, who attended Ruk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
1
11
1
Order By: Relevance
“…RDTs targeting HRP2 are specific for the detection of P. falciparum , while RDTs targeting LDH can be used for the detection of P. falciparum , P. vivax , or pan-specific (e.g., four Plasmodium species) LDH antibodies; aldolase is another common target for RDTs to detect all Plasmodium species 7 10 . Recently used commercial dipsticks for the detection of HRP-2 include PfHRP2 CareStart 11 13 , SD Bioline Malaria Ag Pf 14 , 15 , and SD BIOLINE Malaria Ag P.f/Pan 16 , and one recently used for the detection of pLDH is CareStart pLDH(pan) 15 . A recently used commercial dipstick for the detection of Pan-aldolase is ParaHit Total, while a recently used commercial dipsticks for the detection of P. vivax aldolase is mAb 1C3-12 F10 17 .…”
Section: Introductionmentioning
confidence: 99%
“…RDTs targeting HRP2 are specific for the detection of P. falciparum , while RDTs targeting LDH can be used for the detection of P. falciparum , P. vivax , or pan-specific (e.g., four Plasmodium species) LDH antibodies; aldolase is another common target for RDTs to detect all Plasmodium species 7 10 . Recently used commercial dipsticks for the detection of HRP-2 include PfHRP2 CareStart 11 13 , SD Bioline Malaria Ag Pf 14 , 15 , and SD BIOLINE Malaria Ag P.f/Pan 16 , and one recently used for the detection of pLDH is CareStart pLDH(pan) 15 . A recently used commercial dipstick for the detection of Pan-aldolase is ParaHit Total, while a recently used commercial dipsticks for the detection of P. vivax aldolase is mAb 1C3-12 F10 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in this study mRDT sensitivity >95% was found to be associated with malaria parasites density equal or greater than 100/ μl, a nding that is in agreement with what was found by Biso et al and Nwajei et al(30) (11). This limitation of the current mRDTs led to the development of newer generation of highly-sensitive mRDTs aimed at increasing the capability of mRDTs to detectThe speci city of 98.78% identi ed in this present study was higher than other speci city found in other studies by Niyibizi et al, Anthony et al, Henry et al and Isa et al of 59.2%, 89%, 97% and 89.6% respectively(24) (11)(15)…”
mentioning
confidence: 54%
“…In 2018, a research was carried in kayonza district (Eastern province of Rwanda) and compared the performance of HRP-2 based mRDT and microscopy-based malaria test. This study found that the sensitivity of mRDT was 95.0% while speci city was found to be 59.2% among 264 suspected patients (24) and despite the extensive training of CHWs, the observed value for the speci city was below the acceptable levels. Moreover, little is known about the accuracy and predictive value of mRDT in the diagnosis of malaria infection at community level where asymptomatic people are more likely to have lower parasitaemia than in clinical settings (Vivi Maketa et al 2013) [1].…”
Section: Introductionmentioning
confidence: 68%
“…In 2018, research was carried out in Kayonza District (Eastern Province of Rwanda), and the performance of HRP-2-based mRDT and microscopy-based malaria tests were compared. This study found that the sensitivity of mRDT was 95.0%, while the specificity was 59.2% among 264 suspected patients [24], and despite the extensive training of CHWs, the observed value for the specificity was below the acceptable levels. Moreover, little is known about the accuracy and predictive value of mRDT in the diagnosis of malaria infection at the community level, where asymptomatic people are more likely to have lower parasitaemia than in clinical settings [25].…”
Section: Introductionmentioning
confidence: 66%